ANALISIS KINERJAKEUANGAN PERBANKAN TERHADAP NILAI PERUSAHAAN DENGAN ROA SEBAGAI VARIABEL INTERVENING - Diyah Santi Hariyani (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2018)
Purpose this study analyze Financial Performance to firm value with ROA as intervening variable. Quantitative research, with purposive sampling method of banking companies listed on the BEI 2012-2014, which meets the criteria has been selected as a sample of 11 companies. To analyze data by Least Square (PLS) approach. Hypothesis testing in this study using path analysis and sobel test. Results of this research: CAR, NPL, NIM, LDR and BOPO have a significant effect on ROA. CAR, LDR and ROA have a significant positive effect on firm value. NPL, NIM, BOPO have no effect on company value. And ROA is variable able to mediate the influence of CAR, NPL, NIM, LDR and BOPO to firm value.